Mechanism of transmethylation in anisole decomposition over HZSM-5: Experimental study - Zhang, Jiajun; Fidalgo Fernandez, Beatriz; Shen, Dekui; Xiao, Rui; Gu, Sai (Elsevier, 2016)
This work investigated the decomposition of anisole (methoxyl-based lignin model compound) in a fluidized bed reactor over no catalysts and a series of HZSM-5 zeolite catalysts with different Si/Al atomic ratios. Transmethylation reaction was identified as the initial step of the thermal decomposition of anisole, leading to the prominent production of phenolic compounds. Methyl phenols were identified as the main products, with the yield of o-cresol being higher than that of p-cresol at the temperatures below 600° C. The transmethylation reaction over HZSM-5 zeolite catalyst was found to occur at temperatures 150° C lower than those for non-catalytic reaction, with the yield of the phenolic compounds being promoted by 2.5 times. Production of the main phenolic compounds during the catalytic decomposition of anisole was enhanced to different extents depending on the Si/Al ratio. The highest selectivity of 79 wt.% was achieved over the zeolite catalyst with a Si/Al ratio of 80. The Brønsted acid sites of the catalyst played a significant role in both the preferential formation of phenolic compounds and preservation of the methyl group.
Keywords: Mechanism; Anisole; Transmethylation; Phenolic compounds; Brønsted acid; Catalytic decomposition